Feasibility of combining dental hypnosis and tell–show–do in pediatric dentistry - Gusti Agung Intan Pratiwi; Ratna Indriyanti; Gilang Yubiliana; Tantry Maulina; Arlette Suzy Setiawan (Dental Journal (Majalah Kedokteran Gigi), 2026)
Background: Dental hypnosis is a behavioral management technique that holds potential but is associated with certain challenges in pediatric dentistry. Purpose: This study evaluated the practicality and acceptability of integrating the tell–show–do (TSD) technique with dental hypnosis to manage fear and pain during local anesthesia. Methods: A quasi-experimental study involving 16 children who received behavioral support through TSD and hypnosis prior was conducted. The children were matched for age and sex to form a control group that received only TSD. Fear and pain were assessed using the Facial Image Scale and the Face, Leg, Activity, Cry, Consolability scale, respectively. The data were analyzed using the Wilcoxon test and the Mann–Whitney U test. Results: The combination of TSD and dental hypnosis significantly reduced fear (p = 0.0028). However, changes in pain perception between groups were not statistically significant (p = 0.113 and p = 0.3272 for fear and pain, respectively). Conclusion: Dental hypnosis combined with TSD is a promising approach for reducing fear and pain in children.